Transport Methods and Their Impact on the Growth of Residential Use in the City of Kufa - Helen Mohammed Abdel Hussein Al-Bdairi; Prof. Dr. Hussein Jaaz Nasser Al-Fatlawi; Muhammad Lotfi Zaki Ali (Zien Journals, 2023)
The city is unique among human communities and has special significance. The town is a partial system represented by how each resident exercises their role, and this interdependence and the unpredictability it generates are hallmarks of the city's objective complexity. From a functional standpoint, which guarantees the state of attraction with other services through its operating performance, it enables the development process that is only possible with knowledge and understanding of the nature of use as a location and distribution. Career despite the continuous change according to the constantly updated requirements of the individual according to the process of constant mobility, and from that, we deal with the interconnected process between the movement artery within the city and between residential use or urban expansion, as the policies of countries today are concerned with infrastructure, the most important of which is transport methods to defuse the momentum from densely populated areas. Simultaneously, we establish. The lack of effective streets and their inception without previous planning are problems in many Iraqi cities.
Keywords: effective; streets; without; interconnected